IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE STAD BERMODIFIKASI MAKE A MATCH TERHADAP UPAYA PENCAPAIAN KETUNTASAN BELAJAR EKONOMI PADA SISWA KELAS X SMA NUSANTARA INDAH, SINTANG, KALIMANTAN BARAT - Yulia Suriyanti; Trisno Martono; Asri Laksmi Riani (Jurnal Pendidikan Insan Mandiri, 2014)
The learning process which is monotonous and which is not varied results in the students’ low mastery of the learning material. The learning process which does not pay attention to some supporting factors such as the students’ initial condition, learning motivation, learning interest, and learning activities will also have implications on their learning achievement which is low as indicated by their low scores. As a result, their learning completeness cannot maximally be accomplished. The objectives of this research are to apply the use of the cooperative learning of STAD type with Make A Match modification supported by the students’ initial ability, learning motivation, learning interest, and learning activities on the accomplishment of their Economics learning completeness.This research used the classroom action research. It was conducted in two cycles at Nusantara Indah Senior Secondary School of Sintang, West Kalimantan. The subjects of the research were the students in Grade XE of the school. The data of the research were gathered through observation, test, questionnaire, and in-depth interview, and documentation. They were then descriptively   analyzed by comparing the results of each cycle.The results of the research are as follows. Prior to the treatment, the percentage of the students who accomplish the Economics learning completeness is 13.15% with the score of their initial learning interest of 77.24 (low category), that of the learning motivation of 63.23 (low category), and that of the learning activities of 61.15 (low category). Following the treatment, the percentage of the students who accomplish the Economics learning completeness becomes 51.42% in Cycle I with the score of their initial learning interest of 93.31 (high category), that of the learning motivation of 70.51 (high category), and that of the learning activities of 67.85 (low category) and 91.42% in Cycle II with the score of their initial learning interest of 114.77 (high category), that of the learning motivation of 90.17 (high category), and that of the learning activities of 89.74 (high category). Based on the results of the research, a conclusion is drawn that there is an improvement in the students’ final average score.